Getting the balance right: can smart thermal storage work for both customers and grids? - Darby, S; Higginson, S; Topouzi, M; Goodhew, J; Reiss, S (Real Value Project, 2018)
‘Can smart electric thermal storage work for customers and the grid?’ An answer, based on RealValue findings, is ‘Yes, provided certain conditions are met’. Some of these conditions will be regulatory and some will relate to grid and local network conditions. Several relate directly to the customers who rely on the storage devices for warmth and hot water. At the end of what has been a complex demonstration project, offering many new and valuable insights, the best outcomes for customers have come from a combination of reasonable expectations, reliable technology, skilled middle actors and well-planned, diverse forms of engagement with technology and with people.